Improving Oil Supply Security: Using a Risk Optimization Model to China and India - Ming Qi; Danyang Shi; Congcong Li; Jialu Wu; Pei Wang (Discrete Dynamics in Nature and Society)
In this paper, a risk optimization model is proposed to minimize the oil supply risk from the perspective of diversification. The results show that there is large room for both China and India to improve the oil supply security. China should reduce oil imports from Saudi Arabia and Russia while increasing oil imports from the United States and Kazakhstan. India should import more oil from America and Russia while substantially reducing imports from Iraq and Saudi Arabia. In terms of the regional analysis, the Middle East plays a crucial role in the oil import strategies. They account for almost half of the total oil imports to China and India. African countries provide an alternative choice to diversify their energy supply risks. Based on forecasts of oil demand, we investigate the optimal oil import strategies for both countries until 2030 and 2040. China’s imports from the United States and Kazakhstan are forecasted to increase by more than ten times by 2030. India should import four times as much oil from the United States as it does now and import 10 times more crude oil from Russia. Africa and North America will play a more important role in India’s oil supply security.